Pengaruh Tingkat Language Talent Siswa dan Pengaruhnya terhadap Prestasi serta Motivasi Belajar Fikih - Fauziah; Binti Nasukah (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2022)
Fiqh learning is one of the Islamic religious materials that must be taught in madrasas. Researchers and practitioners of fiqh material try to find factors that can increase learning achievement and motivation. There is an assumption that one of the factors that determines the mastery of learning fiqh is the possession of language talent. Based on these assumptions, the study aims to determine whether the level of students' language talent has an impact on their learning achievement and motivation, by first disclosing the level of language proficiency, the level of learning achievement and the level of motivation to study specifically in Islamic Jurisprudence subjects. The research uses quantitative types with data collection techniques through questionnaire surveys for language aptitude variables and through documentation for students' learning achievement variables. The research was conducted on MTsN students in Malang Regency, with a sample of 122 respondents. The data obtained was then analyzed using a relationship test (causal) through linear regression. The results show that there is an influence of language talent on improving student achievement and motivation. This finding has implications for obtaining an important factor that must be considered by Fiqh teachers in an effort to improve their students' learning achievement and motivation, namely the factor of language talent.